Increased Emotional and Behavioral Problems in Children During Covid-19 Pandemic - Nurul Istiqomah (IKesT Muhammadiyah Palembang, 2024)
Introduction. Efforts made to control the pandemic can have a significant impact on the economic sector, daily activities and all aspects of children's lives. The impact that occurs can last a lifetime. The health risk due to COVID-19 infection in children may be lower than in older age groups, there are 80 million children in Indonesia (around 30% of the entire population) who have the potential to experience serious impacts due to various secondary impacts that arise both in the short term and long-term. Therefore, the aim of this research is to determine the factors that influence children's behavioral and emotional problems during the Covid-19 Pandemic. Method. The research used a cross sectional design and the sampling technique used purposive sampling of 102 respondents. Data analysis using chi-square or Fisher was followed by multivariate analysis using multivariate logistic regression analysis. Result. This research found that parents' mental health was the factor most related to children's behavior with a significant value (p-value) of 0.028, less than 0.05. Discussion. Children who are exposed to stressors with parents who experience mental health problems will affect the child's future life as an adult.